Un courant d’Est venu à l’Ouest via l’adaptateur scénique Virgil Tănase - PLESANU, Ondine (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
The article An Eastern current coming to the West, through Virgil Tănase’s stage adaptations addresses the influences of two literary and theatrical cultures from the East (Romania and Russia) on the work of Virgil Tănase as a stage adapter in France. By scrutinizing the way in which the great Russian authors from the 19th century to the present day through the Soviet era establish themselves as a frame of reference for Tănase’s work as a stage adapter and by addressing the way in which this comes to fruition, within the stage adaptations created in France by the Franco-Romanian writer (often performed abroad too), a dreamlike aesthetic born in Romania in the 1960s, the study will show that Virgil Tănase, also known as a translator, managed to create a scenic poetics in which the words are at the service of the melody just as the scenography is at the service of the theatrical metaphor. By highlighting the ontological scope of the character and especially the actor, the stage adaptations developed by Tănase from canonical works of Eastern and Western literature finally converge towards a common goal, representative of his writer’s gesture: all aim to awaken in spectators their freedom to think and create, to revive each person’s faith in the fulfilment of their vocation, like the Proustian narrator of the novel In Search of Lost Time.